New metastatic model of human small‐cell lung cancer by orthotopic transplantation in mice. Issue 4 (26th February 2015) - Sakamoto, Shuichi; Inoue, Hiroyuki; Ohba, Shunichi; Kohda, Yasuko; Usami, Ihomi; Masuda, Tohru; Kawada, Manabu; Nomoto, Akio
Abstract : Small‐cell lung cancer (SCLC) is an aggressive cancer with high metastatic ability and novel strategies against the metastasis are urgently needed to improve SCLC treatment. However, the mechanism of metastasis of SCLC remains largely to be elucidated. For further studies of SCLC metastasis, we developed a new orthotopic transplantation model in mice. We established a GFP‐labeled subline from the human SCLC cell line DMS273 and transplanted them orthotopically into the lung of nude mice with Matrigel. The GFP‐labeled cells showed significant metastatic activity and formed metastatic foci in distant tissues such as bone, kidney, and brain, as observed in SCLC patients. From a bone metastasis focus of the mouse, we isolated another subline, termed G3H, with enhanced metastatic potential and higher hepatocyte growth factor (HGF) expression than the parental line. Further studies indicated that the HGF/MET signaling pathway was involved in in vitro motility and invasion activities of the G3H cells and treatments with MET inhibitors decreased formation of distant metastases in our orthotopic model using G3H cells. These data indicated that our model mimics the clinical aspect of SCLC such as metastatic tropism and autocrine of HGF/MET signaling. Compared with other orthotopic SCLC models, our model has a superior ability to form distant metastases. Therefore, our model will provide a valuable tool for the study of SCLC metastasis. Abstract : Orthotopic and metastatic tumor formation of G3H, a GFP‐labelled human SCLC DMS273 cell line, in nude mice. Intrapulmonary injected cells formed tumor at an injected site of lung and metastatic colonies in various distant organs.